2018
DOI: 10.1038/s41598-018-21215-1
|View full text |Cite
|
Sign up to set email alerts
|

Applying Data-driven Imaging Biomarker in Mammography for Breast Cancer Screening: Preliminary Study

Abstract: We assessed the feasibility of a data-driven imaging biomarker based on weakly supervised learning (DIB; an imaging biomarker derived from large-scale medical image data with deep learning technology) in mammography (DIB-MG). A total of 29,107 digital mammograms from five institutions (4,339 cancer cases and 24,768 normal cases) were included. After matching patients’ age, breast density, and equipment, 1,238 and 1,238 cases were chosen as validation and test sets, respectively, and the remainder were used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 27 publications
(19 reference statements)
1
46
0
Order By: Relevance
“…In radiology.rsna.org n Radiology: Volume 00: Number 0-2018 similar to that of the radiologist with the lowest performance in enriched and selected data sets, but only in very limited scenarios (eg, only soft-tissue lesions). A study by Kim et al (33) found that in-house-developed AI algorithms achieved a sensitivity of 76% and a specificity of 89% in a screening data set. Despite the differences in data sets, our results support the observed trend that AI algorithms are reaching a performance similar to that of radiologists for breast cancer detection in mammography.…”
Section: Discussionmentioning
confidence: 99%
“…In radiology.rsna.org n Radiology: Volume 00: Number 0-2018 similar to that of the radiologist with the lowest performance in enriched and selected data sets, but only in very limited scenarios (eg, only soft-tissue lesions). A study by Kim et al (33) found that in-house-developed AI algorithms achieved a sensitivity of 76% and a specificity of 89% in a screening data set. Despite the differences in data sets, our results support the observed trend that AI algorithms are reaching a performance similar to that of radiologists for breast cancer detection in mammography.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, a study using a CNN system was designed to differentiate between normal and abnormal images via biomarkers such as breast density, presence of mass and microcalcification . Their results indicated that abnormal images were more accurately identified when microcalcifications and benign cases were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that due to the training data having an uneven number of cases of normal and cancer cases, this caused overfitting and database dependency. This creates difficulty distinguishing between benign and malignant cases due to overreliance on heuristics and an inability to learn and adapt from new cases …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the inability to identify malignant lesions limits its ability to perform as an independent reader. Finally, Kim et al developed a system which made a malignancy prediction on an entire mammography case (all 4 views) [25]. The model was trained on malignant (biopsy proven) and normal (with at least 2 years of negative followup) cases from multiple hardware vendors.…”
Section: The Promise Of Deep Learningmentioning
confidence: 99%